Seguimiento de Glucosa Basal y Hemoglobina Glicosilada a pacientes del Club de Diabéticos del Subcentro de Salud de Malacatos. - Guerrero Córdova, Rosa Irma (2013)
This study called "BASAL AND GLUCOSE MONITORING glycosylated hemoglobin A DIABETIC PATIENTS CLUB HEALTH sub center Malacatos" is a descriptive cross was put into effect during the months of August to October 2012, in the Sub-center of Malacatos parish of the city of Loja, the sample consisted of 46 patients diagnosed with type 2 diabetes, for which we performed analysis of basal glucose and glycosylated hemoglobin in order to determine the adequate control of the disease, to take effect diabetes monitoring proceeded to the weekly determination of glucose, established that 57% showed increased levels of glucose (> 110mg/dl), while 96% were for glycosylated hemoglobin (HbA1c), therefore there is a poor control of the disease, which is corroborated by glucose monitoring on a weekly basis, the months of August, September and October. So in August the 63% of the study population presented increased levels of glucose (> 110mg/dl), in September by 61%, while in October the 61%. Following laboratory tests related glycosylated hemoglobin and fasting glucose, determined that 60,87% of patients showed increased basal glucose and 96% for glycosylated hemoglobin (> 7%), the present work shows clearly inadequate control by the 46 participants, for best quality of life of diabetic patients , it gave a talk to staff this home health care, where it is recommended that all patients diagnosed with type 2 diabetes should be performed glycosylated hemoglobin test every 3 months as well as the determination of baseline fasting glucose on a weekly or monthly basis for the purpose of keep adequate metabolic control but no laboratory test will be critical if not maintaining abaladiet, exercise and a good treatment by the clinician. Keywords: basal glucose, glycated hemoglobin, diabetes patients